A novel output redefinition method for nonlinear H∞ attitude stabilization of a flexible spacecraft - Majid Esmaeilzadeh, Seyed; Sadegh Zeyghami, Mohammad (Asian journal of control, 2024)
This paper addresses a novel output redefinition method for the nonlinear H∞$$ H_{∞ } $$ attitude stabilization problem of a flexible spacecraft. As an idea, the flexible appendage tip‐point can be selected as attitude output which may improve attitude pointing accuracy. However, it makes the system non‐minimum phase. The output redefinition method is an effective method to make the system minimum phase. In this paper, a novel output redefinition is proposed to overcome the non‐minimum phase property such that it improves the attitude control system performance. Then, a nonlinear H∞$$ H_{∞ } $$ controller is designed based on back‐stepping approach and a modal observer. The simulation results show the effectiveness of the proposed method in the presence of model uncertainties and environmental disturbances.